Preparation method of intelligent anti-icing coating for power transmission line

Through the combination of near-infrared photothermal filler and graded heat storage and deicing filler, an intelligent anti-icing coating is constructed, which solves the problem of performance degradation of existing coatings under extreme conditions and achieves continuous under light and light-free conditions Anti-ice covering effect improves the anti-ice covering performance and service life of the cable.

CN119192945AActive Publication Date: 2024-12-27XIAN UNIV OF TECH

Patent Information

Application Number
CN202411330343.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing anti-ice coating is easily occupied by ice under extreme conditions, and the superhydrophobic properties are lost. The photothermal coating is greatly affected by the weather, and the continuous anti-ice coating is not effective.

Method used

Using near-infrared photothermal fillers and graded heat storage and deicing fillers, epoxy resins, silane coupling agents, etc., to build an intelligent anti-ice coating, and adsorbing iodine vapor and phase-changing microcapsules through hydroxylated boron nitride nanosheets , form an uneven superhydrophobic surface, expand the photothermal spectrum and store heat to achieve continuous ice melting effect.

Benefits of technology

It reduces the bonding force between ice and coating, improves the photothermal performance and service life, ensures that ice covering can be effectively prevented under light and light conditions, and enhances the anti-ice covering performance of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192945A_ABST
    Figure CN119192945A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an intelligent anti-icing coating for a power transmission line, which comprises the following steps: firstly preparing a near-infrared photothermal filler and a graded heat storage deicing filler, and then mixing and stirring the near-infrared photothermal filler and the graded heat storage deicing filler with epoxy resin, a silane coupling agent, a curing agent, a defoaming agent and a solvent to obtain the intelligent anti-icing coating. And finally, uniformly spraying the intelligent anti-icing coating on the cable, and carrying out high-temperature curing treatment to obtain the intelligent anti-icing coating. The non-uniform surface formed by different size grading and silane hydrophobic modification reduces the binding force between the ice coating and the coating; the near-infrared photothermal filler expands a photothermal spectrum to a near-infrared part, and meanwhile, the high thermal conductivity of the near-infrared photothermal filler is convenient for transferring heat to the surface ice melting and heat storage deicing filler to store the heat, so that the photothermal performance is improved; the photo-thermal material can absorb heat of the sunlight conversion layer in a wide spectrum to directly melt the ice layer, and part of the heat is stored in the phase change material to realize continuous ice melting through phase change heat release under the dark condition, so that the service life of the cable is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of anti-icing, and in particular relates to a method for preparing an intelligent anti-icing coating for a power transmission line. Background Art

[0002] Ice-covering phenomena such as precipitation ice-covering and sublimation ice-covering are very common in nature. In most cases, the formation of ice-covering will bring great inconvenience to people's production and life. Its continuous attachment and accumulation on vehicles and external equipment will cause traffic obstruction and equipment damage. Among them, rain with lower temperature will freeze when it falls on transmission lines below zero degrees, which is called transmission line ice-covering. Transmission line ice-covering is one of the most serious disasters in the power system. Ice-covering can cause ice flash, overload, line dancing, and even line breakage and tower collapse in the power system, which seriously threatens the safe operation of the power grid. In order to avoid or reduce the harm caused by ice-covering of transmission lines, in addition to improving the standards for the anti-icing design of power grid lines, we should also actively consider the use of anti-icing or de-icing technology.

[0003] By using anti-icing coating to construct a coating on the surface of the transmission line, the formation and growth of ice on the transmission line can be actively suppressed and alleviated during the icing period, which can fundamentally eliminate the occurrence of icing disasters on the transmission line. The anti-icing coating method is a promising method for anti-icing of transmission lines because of its low energy consumption and easy implementation. At present, researchers have developed many anti-icing coatings, most of which are based on micro-nano structures, super-hydrophobic surfaces, photothermal effects, electric heating and deicing principles. However, under extreme conditions, the super-hydrophobic surface ice based on the micro-nano structure forms a mechanical interlock with the rough structure of the super-hydrophobic surface, which is more difficult to remove later; at the same time, the anti-icing coating with photothermal effect is greatly affected by the weather, and the continuous anti-icing effect is not good. Therefore, it is of great significance to national security and economic development to provide an anti-icing coating with super-hydrophobicity, low ice adhesion and intelligent photothermal ice melting performance.

[0004] Zhu et al. (Tao Zhu, Yuan Yuan, Huiying Xiang, et al, A composite pore-structured superhydrophobic aluminum surface for durable anti-icing, Journal of Materials Research and Technology, 27, 2023, 8151-8163.) prepared a composite pore structure by a two-step anodization method and successfully constructed a SHP self-healing anti-icing surface with a composite pore structure on aluminum. The hierarchical pore structure improved the durability of the coating and had good anti-icing performance, but the superhydrophobic surface was easily occupied by ice, causing the surface to lose its superhydrophobic properties, thereby causing the surface to lose its anti-icing performance.

[0005] The Chinese patent "Anti-icing coating, preparation method and application thereof" (application number: CN202410349819.2, publication number: CN118421140A, publication date: 2024.08.02) discloses an anti-icing coating, preparation method and application thereof, which chemically modifies fluorocarbon resin through polysiloxane polymer to introduce silicon-containing groups on the main chain or side chain of fluorocarbon polymer to form block, graft or interpenetrating network copolymers. The added lubricant makes the film have a smooth covering layer, which can isolate ice water from the surface of the anti-icing film, thereby significantly reducing the ice adhesion on the surface of the anti-icing film, and has good anti-icing performance. However, there are problems such as lack of active ice melting and lubricant consumption, and the long-term anti-icing performance in extreme environments is insufficient.

[0006] The Chinese patent "A nano anti-icing coating and its preparation method" (application number: CN202410824858.3, publication number: CN118374195A, publication date: 2024.07.23) discloses a nano anti-icing coating and its preparation method. First, nano SiO2 balls are prepared, and then silane and dendritic macromolecules are grafted on the surface of nano SiO2 balls and porous fillers respectively to prepare an anti-icing coating with super double repellency and strong binding force, which has good anti-icing performance. However, there is a single micro-nano structure, no active ice melting problem, and insufficient long-term anti-icing performance in extreme environments.

[0007] The Chinese patent "An anti-icing coating, anti-icing material and preparation method thereof" (application number: CN201911108251.0, authorization announcement number: CN110804395B, authorization publication date: 2021.09.21) discloses an anti-icing coating, an anti-icing material and a preparation method thereof, wherein the base material is placed in iodine vapor for adsorption treatment, and then the anti-icing coating is sprayed on the base material after adsorption treatment, and the excellent photothermal properties of iodine vapor are used to achieve active photothermal deicing and passive anti-icing, which has good anti-icing performance. However, the hydrophobic performance is insufficient, the ice melting effect is greatly affected by the weather, and the continuous anti-icing effect is not good. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing an intelligent anti-icing coating for transmission lines, which solves the problems in the prior art that the super-hydrophobic surface of the anti-icing coating is easily occupied by ice, the photothermal coating is greatly affected by the weather, and the continuous anti-icing effect is poor.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] A method for preparing an intelligent anti-icing coating for a transmission line is specifically implemented according to the following steps:

[0011] Step 1, preparation of near-infrared photothermal filler:

[0012] Boron nitride and glucose are loaded into a ball mill according to a proportion, and hydroxylated boron nitride nanosheets are obtained after ball milling and centrifugal drying. The obtained hydroxylated boron nitride nanosheets are placed in a glass culture dish, and then the culture dish is placed in a saturated iodine vapor sealed environment for iodine vapor adsorption, and then the hydroxylated boron nitride nanosheets are ultrasonically cleaned with anhydrous ethanol, and dried for standby use to obtain near-infrared photothermal fillers;

[0013] Step 2, preparing graded heat storage and deicing filler;

[0014] The phase change material, emulsifier, deionized water and surfactant are uniformly mixed in proportion, and uniformly stirred at a certain temperature to obtain a phase change material emulsion, and then TEOS and a catalyst are added dropwise to the phase change material emulsion and stirred to obtain a phase change microcapsule solution, and the phase change microcapsules are obtained after washing and drying, and the phase change microcapsules are dispersed in a 5%wt. HCl solution of polyaniline, heated and stirred, and washed and dried to obtain a graded heat storage deicing filler;

[0015] Step 3: Prepare the smart anti-icing coating:

[0016] The near-infrared photothermal filler obtained in step 1 and the graded heat storage deicing filler obtained in step 2 are mixed with epoxy resin, solvent and silane coupling agent to make the filler dispersed evenly, and then a curing agent and a defoaming agent are added and stirred to obtain an intelligent anti-icing coating;

[0017] Step 4: Build an intelligent anti-icing coating:

[0018] Add the intelligent anti-icing coating obtained in step 3 into the spray gun, spray the prepared intelligent anti-icing coating vertically on the cable, and place the cable sprayed with the intelligent anti-icing coating in a blast drying oven for curing, so as to prepare the intelligent anti-icing coating on the surface of the cable.

[0019] Furthermore, in step 1, the ratio of boron nitride to glucose is 10 to 1:1, wherein the adsorbed iodine vapor is obtained by sublimation of elemental iodine, and the adsorption temperature is 80 to 120°C.

[0020] Furthermore, the phase change material emulsion prepared in step 2 is composed of the following substances in percentage by mass: 10% to 25% of phase change material, 5% to 15% of emulsifier, 3% to 10% of surfactant, and 50% to 82% of deionized water, and the sum of the above components is 100%.

[0021] Furthermore, in step 2, the phase change material is any one of dodecane, methyl laurate, decanol, and tetradecane, the emulsifier is a span-80 and tween-80 complex in a mass ratio of 1:1, and the surfactant is any one of PVA and CTAB.

[0022] Furthermore, the phase change microcapsule solution prepared in step 2 is composed of the following substances by mass percentage: 75% to 92% of phase change material emulsion, 7% to 20% of TEOS, and 1% to 5% of catalyst, and the sum of the above components is 100%.

[0023] Furthermore, the catalyst in step 2 is one of acetic acid and ammonia water, and the reaction temperature for preparing phase change microcapsules is 25-50°C.

[0024] Furthermore, in step 2, the mass ratio of the phase change microcapsules to the 5 wt.% HCl solution of polyaniline is 1:50-200, and the diameter of the graded heat storage and deicing filler is 100 nm-1 um.

[0025] Furthermore, in step 3, the intelligent anti-icing coating is composed of the following substances in mass percentage: 1% to 10% near-infrared thermal filler, 1% to 10% graded heat storage deicing filler, 25% to 35% epoxy resin, 1% to 5% silane coupling agent, 0.5% to 1% curing agent, 0.5% to 1% defoaming agent, 48% to 71% solvent, and the sum of the above components is 100%.

[0026] Furthermore, the diameter of the graded heat storage and deicing filler is 100nm:1um, which is 5 to 1:1; the silane coupling agent is any one of KH-570, KH-560, and KH-580; the solvent is any one of ethanol, DMF, and DMSO; the curing agent is any one of polyamide and tertiary amine; and the defoaming agent is one of fatty alcohol ethoxysiloxane and polyether siloxane.

[0027] Furthermore, in step 4, the spraying speed is 10-30 m / min, the spraying distance is 20-50 mm, the curing time is 30-60 min, and the curing temperature is 50° C.-150° C.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] A method for preparing an intelligent anti-icing coating for a power transmission line. The uneven surface formed by different size classifications and silane hydrophobic modification reduces the bonding force between the ice and the coating. The near-infrared photothermal filler expands the photothermal spectrum to the near-infrared part, and its own high thermal conductivity facilitates the transfer of heat to the surface ice melting and heat storage deicing filler to store heat, thereby improving the photothermal performance. The photothermal material can absorb the heat of the solar light conversion layer in a wide spectrum to directly melt the ice layer, and store a part of the heat in the phase change material to achieve phase change heat release and continuous ice melting in the absence of light, thereby enhancing the service life of the cable and having important application prospects in the field of cable anti-icing. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the morphology of the intelligent anti-icing coating prepared by the present invention.

[0031] In the attached figure, 1-cable substrate, 2-intelligent anti-icing coating, 3-graded heat storage and deicing filler, 4-near-infrared photothermal filler, 5-hydroxylated boron nitride nanosheets, 6-iodine (I), 7-polyaniline, 8-SiO2, 9-phase change material. DETAILED DESCRIPTION

[0032] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0033] A method for preparing an intelligent anti-icing coating for a transmission line is specifically implemented in the following steps:

[0034] Step 1, preparation of near-infrared photothermal filler:

[0035] Boron nitride and glucose are loaded into a ball mill at a ratio of 10 to 1:1, and hydroxylated boron nitride nanosheets are obtained after ball milling for 8 hours and centrifugal drying. The obtained hydroxylated boron nitride nanosheets are placed in a glass culture dish, and then placed in a closed environment of iodine vapor to obtain saturated iodine vapor by sublimation of elemental iodine, and iodine vapor is adsorbed at 80 to 120°C for 12 hours. Subsequently, the boron nitride nanosheets are ultrasonically cleaned with anhydrous ethanol for 30 minutes, dried for use, and near-infrared photothermal fillers are obtained.

[0036] Step 2, preparing graded heat storage and deicing filler;

[0037] According to the mass percentage: phase change material 10% to 25%, emulsifier 5% to 15%, surfactant 3 to 10%, deionized water 50% to 82%, they are mixed and stirred evenly at a certain temperature to obtain a phase change material emulsion, and then according to the mass percentage of the phase change material emulsion is 75% to 92%, TEOS is 7% to 20%, and catalyst is 1 to 5%, TEOS and catalyst are added dropwise to the phase change material emulsion and stirred for 3 hours to obtain a phase change microcapsule solution, and phase change microcapsules are obtained after washing and drying, and the phase change microcapsules are dispersed in a 5% wt. HCl solution of polyaniline at a mass ratio of 1:50 to 200, heated and stirred, and a graded heat storage and deicing filler with a diameter of 100nm to 1um is obtained after washing and drying.

[0038] The phase change material is any one of dodecane, methyl laurate, decanol, tetradecane, etc., the emulsifier is a span-80 and tween-80 complex in a mass ratio of 1:1, the surfactant is any one of PVA, CTAB, etc., the catalyst is one of acetic acid, ammonia water, etc., and the reaction temperature for preparing phase change microcapsules is 25-50°C.

[0039] Step 3: Prepare the smart anti-icing coating:

[0040] The near-infrared thermal filler obtained in step 1 and the graded heat storage deicing filler obtained in step 2 are mixed with epoxy resin, solvent and silane coupling agent in the following mass percentages: 1% to 10% of near-infrared thermal filler, 1% to 10% of graded heat storage deicing filler, 25% to 35% of epoxy resin, 1% to 5% of silane coupling agent, 0.5% to 1% of curing agent, 0.5% to 1% of defoaming agent, and 48% to 72% of solvent, and mixed and stirred to evenly disperse the filler to obtain an intelligent anti-icing coating.

[0041] The diameter of the graded heat storage and deicing filler is 100nm:1um, which is 5 to 1:1; the silane coupling agent is any one of KH-570, KH-560, KH-580, etc.; the solvent is any one of ethanol, DMF, DMSO, etc.; the curing agent is any one of polyamide, tertiary amine, etc.; the defoaming agent is one of fatty alcohol ethoxysiloxane, polyether siloxane, etc.

[0042] Step 4: Build an intelligent anti-icing coating:

[0043] Add the intelligent anti-icing coating obtained in step 3 to the spray gun, spray the prepared intelligent anti-icing coating vertically on the cable, and place the cable sprayed with the intelligent anti-icing coating in a blast drying oven to dry, so as to prepare the intelligent anti-icing coating on the surface of the cable. The spraying speed is 10-30m / min, the spraying distance is 20-50mm, the curing time is 30min-60min, and the curing temperature is 50℃-150℃.

[0044] Figure 1 Schematic diagram of the morphology of the intelligent anti-icing coating prepared by the present invention. Figure 1 It can be seen that the intelligent anti-icing coating 2 is attached to the cable substrate 1, and 6-iodine (I) 6 is adsorbed onto the hydroxylated boron nitride nanosheets 5 to form a near-infrared photothermal filler 4, which gives it near-infrared photothermal response performance; the graded heat storage deicing filler 3 is composed of phase change material 9, SiO28 and polyaniline 7 from the inside to the outside. SiO2 encapsulates the phase change material to prevent leakage, and the surface polyaniline is modified to obtain a photothermal response effect. The graded energy storage deicing filler and the near-infrared photothermal filler form an uneven super-hydrophobic surface on the coating, which effectively solves the problem of high adhesion after ice coating. From the planed surface diagram of the graded energy storage deicing filler, it can be seen that the phase change material is encapsulated in the high latent heat SiO2, which can emit heat through phase change for a long time in the absence of light, and has a long-term anti-icing effect.

[0045] The present invention obtains a photothermal filler responsive to near-infrared light by adsorbing iodine vapor through hydroxyl-modified boron nitride nanosheets, obtains a photothermal filler responsive to visible light by coating polyaniline on the surface of phase change microcapsules, controls its photothermal efficiency by adjusting the iodine vapor adsorption amount and the polyaniline coating amount, and thus adjusts its photothermal ice-melting performance under light irradiation; controls the ratio of micro / nano sizes of graded intelligent anti-icing fillers, adjusts the addition amount of silane coupling agent and graded intelligent anti-icing fillers, constructs an uneven graded super-hydrophobic surface, improves the phenomenon that moisture on a traditional uniform micro-nano surface easily condenses into ice inside a rough structure, and the adhesion is enhanced, thereby improving the anti-icing and ice-melting desorption performance; selects different phase change materials and encapsulates them inside a SiO2 ball with high latent heat, adjusts the addition amount of phase change materials to utilize the high heat transfer capacity of boron nitride nanosheets, efficiently improves its phase change heat storage capacity, and improves its phase change anti-heat ice-melting effect in the absence of light.

[0046] The present invention reduces the bonding force between ice and coating by forming an uneven surface through different size classification and silane hydrophobic modification; the near-infrared photothermal filler expands the photothermal spectrum to the near-infrared part, and at the same time its own high thermal conductivity facilitates the heat transfer to the surface ice melting and heat storage deicing filler to store heat, thereby improving the photothermal performance; the photothermal material can absorb the heat of the solar light conversion layer in a wide spectrum to directly melt the ice layer, and store part of the heat in the phase change material to achieve phase change heat release and continuous ice melting in the absence of light, thereby enhancing the service life of the cable, and has important application prospects in the field of cable anti-icing.

[0047] Example 1

[0048] Boron nitride and glucose were loaded into a ball mill at a ratio of 5:1, and hydroxylated boron nitride nanosheets were obtained after ball milling for 8 hours and centrifugal drying. The obtained hydroxylated boron nitride nanosheets were placed in a glass culture dish, and then placed in a closed environment of iodine vapor to obtain saturated iodine vapor by sublimation of elemental iodine, and iodine vapor was adsorbed at 80°C for 12 hours. Subsequently, the boron nitride nanosheets were ultrasonically cleaned with anhydrous ethanol for 30 minutes, dried for use, and near-infrared photothermal fillers were obtained.

[0049] According to the mass percentage, 25% dodecane, 5% span-80 and tween-80 complex with a mass ratio of 1:1 as emulsifier, 3% PVA, and 67% deionized water are mixed and stirred uniformly at 25°C to obtain a phase change material emulsion. Then, according to the mass percentage, the phase change material emulsion is 75%, TEOS is 20%, and the catalyst is 5%. TEOS and acetic acid are added dropwise to the phase change material emulsion and stirred at a temperature of 50°C for 3 hours to obtain phase change microcapsules. After washing and drying, the phase change microcapsules are dispersed in a 5% wt. HCl solution of polyaniline at a mass ratio of 1:200 to the polyaniline hydrochloric acid solution, and heated and stirred. After washing and drying, a graded heat storage and deicing filler with a diameter of 100nm to 1um is obtained.

[0050] The obtained near-infrared thermal filler and graded heat storage and deicing filler are mixed with epoxy resin, solvent and silane coupling agent in mass percentage: 10% near-infrared thermal filler, 5:1 with a diameter of 100nm:1um, 10% graded heat storage and deicing filler, 35% epoxy resin, 5% KH-570, 1% polyamide, 1% fatty alcohol ethoxysiloxane, and 38% ethanol. Mix and stir to make the filler evenly dispersed to obtain an intelligent anti-icing coating.

[0051] The obtained intelligent anti-icing coating was added to the spray gun, and the obtained intelligent anti-icing coating was vertically sprayed on the cable, and dried in a blast drying oven to prepare the intelligent anti-icing coating. The spraying speed was 10m / min, the spraying distance was 50mm, the curing time was 60min, and the curing temperature was 150℃.

[0052] Example 2

[0053] Boron nitride and glucose were loaded into a ball mill at a ratio of 1:1, and hydroxylated boron nitride nanosheets were obtained after ball milling for 8 hours and centrifugal drying. The obtained hydroxylated boron nitride nanosheets were placed in a glass culture dish, and then placed in a closed environment of iodine vapor to obtain saturated iodine vapor by sublimation of elemental iodine, and iodine vapor was adsorbed at 120°C for 12 hours. Subsequently, the boron nitride nanosheets were ultrasonically cleaned with anhydrous ethanol for 30 minutes, dried for use, and near-infrared photothermal fillers were obtained.

[0054] According to the mass percentage, 10% methyl laurate, 15% span-80 and tween-80 complex as emulsifier in a mass ratio of 1:1, 10% CTAB, and 65% deionized water are mixed and stirred uniformly at 25°C to obtain a phase change material emulsion. Then, according to the mass percentage, the phase change material emulsion is 92%, TEOS is 7%, and the catalyst is 1%. TEOS, acetic acid and ammonia water are added dropwise to the phase change material emulsion and stirred for 3 hours at a temperature of 25°C to obtain phase change microcapsules. After washing and drying, the phase change microcapsules are dispersed in a 5% wt. HCl solution of polyaniline in a mass ratio of 1:50 to the polyaniline hydrochloric acid solution, and heated and stirred. After washing and drying, a graded heat storage and deicing filler with a diameter of 100nm to 1um is obtained.

[0055] The obtained near-infrared thermal filler and graded heat storage deicing filler are mixed with epoxy resin, solvent and silane coupling agent in a mass percentage of: 1% near-infrared thermal filler, 1% graded heat storage deicing filler with a diameter of 100nm:1um (1:1), 25% epoxy resin, 1% KH-560, 0.5% tertiary amine, 0.5% polyether siloxane, and 72% DMF. The mixture is stirred to make the filler evenly dispersed to obtain an intelligent anti-icing coating.

[0056] The obtained intelligent anti-icing coating was added to the spray gun, and the obtained intelligent anti-icing coating was vertically sprayed on the cable, and dried in a blast drying oven to prepare the intelligent anti-icing coating. The spraying speed was 30m / min, the spraying distance was 20mm, the curing time was 30min, and the curing temperature was 50℃.

[0057] Example 3

[0058] Boron nitride and glucose were loaded into a ball mill at a ratio of 5:1, and hydroxylated boron nitride nanosheets were obtained after ball milling for 8 hours and centrifugal drying. The obtained hydroxylated boron nitride nanosheets were placed in a glass culture dish, and then placed in a closed environment of iodine vapor to obtain saturated iodine vapor by sublimation of elemental iodine, and iodine vapor was adsorbed at 100°C for 12 hours. Subsequently, the boron nitride nanosheets were ultrasonically cleaned with anhydrous ethanol for 30 minutes, dried for use, and near-infrared photothermal fillers were obtained.

[0059] According to the mass percentage: 10% decanol, 5% span-80 and tween-80 complex with a mass ratio of 1:1 as emulsifier, 3% PVA, 82% deionized water, mix them and stir them evenly at 25°C to obtain a phase change material emulsion, then according to the mass percentage of the phase change material emulsion is 85%, TEOS is 10%, and the catalyst is 5%, TEOS and acetic acid are added dropwise to the phase change material emulsion and stirred at 30°C for 3 hours to obtain phase change microcapsules, after washing and drying, the phase change microcapsules are dispersed in a 5%wt. HCl solution of polyaniline at a mass ratio of 1:100 to the polyaniline hydrochloric acid solution, heated and stirred, and after washing and drying, a graded heat storage and deicing filler with a diameter of 100nm~1um is obtained.

[0060] The obtained near-infrared thermal filler and graded heat storage deicing filler are mixed with epoxy resin, solvent and silane coupling agent in mass percentage: near-infrared thermal filler is 10%, diameter 100nm:1um is 3:1 graded heat storage deicing filler is 10%, epoxy resin is 35%, KH-5805%, tertiary amine is 1%, fatty alcohol ethoxysiloxane is 1%, DMSO is 48%, and mixed and stirred to make the filler evenly dispersed to obtain the intelligent anti-icing coating.

[0061] The obtained intelligent anti-icing coating was added to the spray gun, and the obtained intelligent anti-icing coating was vertically sprayed on the cable, and dried in a blast drying oven to prepare the intelligent anti-icing coating. The spraying speed was 20m / min, the spraying distance was 40mm, the curing time was 45min, and the curing temperature was 120℃.

[0062] Example 4

[0063] Boron nitride and glucose were loaded into a ball mill at a ratio of 10:1, and hydroxylated boron nitride nanosheets were obtained after ball milling for 8 hours and centrifugal drying. The obtained hydroxylated boron nitride nanosheets were placed in a glass culture dish, and then placed in a closed environment of iodine vapor to obtain saturated iodine vapor by sublimation of elemental iodine, and iodine vapor was adsorbed at 120°C for 12 hours. Subsequently, the boron nitride nanosheets were ultrasonically cleaned with anhydrous ethanol for 30 minutes, dried for use, and near-infrared photothermal fillers were obtained.

[0064] According to the mass percentage, 25% tetradecane, 15% span-80 and tween-80 complex with a mass ratio of 1:1 as emulsifier, 10% CTAB, and 50% deionized water are mixed and stirred uniformly at 25°C to obtain a phase change material emulsion. Then, according to the mass percentage, the phase change material emulsion is 80%, TEOS is 12%, and the catalyst is 3%. TEOS and ammonia water are added dropwise to the phase change material emulsion and stirred for 3 hours at a temperature of 45°C to obtain phase change microcapsules. After washing and drying, the phase change microcapsules are dispersed in a 5% wt. HCl solution of polyaniline at a mass ratio of 1:150 to the polyaniline hydrochloric acid solution, and heated and stirred. After washing and drying, a graded heat storage and deicing filler with a diameter of 100nm to 1um is obtained.

[0065] The obtained near-infrared thermal filler and graded heat storage deicing filler are mixed with epoxy resin, solvent and silane coupling agent in mass percentage: 5% near-infrared thermal filler, 5% graded heat storage deicing filler with a diameter of 100nm:1um (2:1), 30% epoxy resin, 3% KH-580, 1% tertiary amine, 1% polyether siloxane, and 55% ethanol. The mixture is stirred to make the filler evenly dispersed to obtain an intelligent anti-icing coating.

[0066] The obtained intelligent anti-icing coating was added to the spray gun, and the obtained intelligent anti-icing coating was vertically sprayed on the cable, and dried in a blast drying oven to prepare the intelligent anti-icing coating. The spraying speed was 10m / min, the spraying distance was 20mm, the curing time was 60min, and the curing temperature was 150℃.

[0067] Table 1 is a comparison of contact angle, ice adhesion, light melting time, time above freezing point temperature after light, and ice adhesion after 50 freeze / thaw cycles of different anti-icing coatings. As can be seen from Table 1, conventional photothermal coatings use all the heat converted by light to melt ice, but the freezing point temperature can only be maintained for a short time after light, which is greatly affected by light. The intelligent anti-icing coatings in Examples 1-4 have improved the photothermal melting performance during illumination due to the synergistic photothermal conversion ability of near-infrared photothermal fillers and graded heat storage deicing fillers, and have a shorter light melting time. Micro / nano-sized SiO2 constructs an uneven graded super-hydrophobic surface, improves the phenomenon that the moisture on the traditional uniform micro-nano surface is easily condensed into ice adhesion inside the rough structure, and has the lowest ice adhesion strength. By encapsulating the phase change material into the interior of the high latent heat SiO2 ball, its phase change heat storage capacity is efficiently improved, and it can still be kept above the freezing point temperature for a long time in the absence of light, thereby improving its phase change anti-heat melting effect in the absence of light.

[0068] Table 1

[0069]

[0070] The above description of the present invention is only a partial embodiment, but the present invention is not limited to the above embodiment. The above embodiment is illustrative and not restrictive. All specific extensions of the materials and methods of the present invention, without departing from the scope of protection of the present invention and the claims, are within the scope of protection of the present invention.

Claims

1. A method for preparing an intelligent anti-icing coating for a power transmission line, characterized in that: Follow the steps below to implement it: Step 1, preparation of near-infrared photothermal filler: Boron nitride and glucose are loaded into a ball mill according to a proportion, and hydroxylated boron nitride nanosheets are obtained after ball milling and centrifugal drying. The obtained hydroxylated boron nitride nanosheets are placed in a glass culture dish, and then the culture dish is placed in a saturated iodine vapor sealed environment for iodine vapor adsorption, and then the hydroxylated boron nitride nanosheets are ultrasonically cleaned with anhydrous ethanol, and dried for standby use to obtain near-infrared photothermal fillers; Step 2, preparing graded heat storage and deicing filler; The phase change material, emulsifier, deionized water and surfactant are uniformly mixed in proportion, and uniformly stirred at a certain temperature to obtain a phase change material emulsion, and then TEOS and a catalyst are added dropwise to the phase change material emulsion and stirred to obtain a phase change microcapsule solution, and the phase change microcapsules are obtained after washing and drying, and the phase change microcapsules are dispersed in a 5%wt. HCl solution of polyaniline, heated and stirred, and washed and dried to obtain a graded heat storage deicing filler; Step 3: Prepare the smart anti-icing coating: The near-infrared photothermal filler obtained in step 1 and the graded heat storage deicing filler obtained in step 2 are mixed with epoxy resin, solvent and silane coupling agent to make the filler dispersed evenly, and then a curing agent and a defoaming agent are added and stirred to obtain an intelligent anti-icing coating; Step 4: Build an intelligent anti-icing coating: Add the intelligent anti-icing coating obtained in step 3 into the spray gun, spray the prepared intelligent anti-icing coating vertically on the cable, and place the cable sprayed with the intelligent anti-icing coating in a blast drying oven for curing, so as to prepare the intelligent anti-icing coating on the surface of the cable.

2. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1, characterized in that: In step 1, the ratio of boron nitride to glucose is 10 to 1:1, wherein the adsorbed iodine vapor is obtained by sublimation of elemental iodine, and the adsorption temperature is 80 to 120°C.

3. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1, characterized in that: The phase change material emulsion prepared in step 2 is composed of the following substances by mass percentage: 10% to 25% of phase change material, 5% to 15% of emulsifier, 3% to 10% of surfactant, and 50% to 82% of deionized water, and the sum of the above components is 100%.

4. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1 or 3, characterized in that: In step 2, the phase change material is any one of dodecane, methyl laurate, decanol, and tetradecane, the emulsifier is a span-80 and tween-80 complex in a mass ratio of 1:1, and the surfactant is any one of PVA and CTAB.

5. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1, characterized in that: The phase change microcapsule solution prepared in step 2 is composed of the following substances by mass percentage: 75% to 92% of phase change material emulsion, 7% to 20% of TEOS, and 1% to 5% of catalyst, and the sum of the above components is 100%.

6. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1 or 5, characterized in that: The catalyst in step 2 is one of acetic acid and ammonia water, and the reaction temperature for preparing phase change microcapsules is 25-50°C.

7. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1, characterized in that: In step 2, the mass ratio of the phase change microcapsules to the 5 wt.% HCl solution of polyaniline is 1:50-200, and the diameter of the graded heat storage and deicing filler is 100 nm-1 um.

8. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1, characterized in that: In step 3, the intelligent anti-icing coating is composed of the following substances in mass percentage: 1% to 10% near-infrared thermal filler, 1% to 10% graded heat storage deicing filler, 25% to 35% epoxy resin, 1% to 5% silane coupling agent, 0.5% to 1% curing agent, 0.5% to 1% defoaming agent, 48% to 71% solvent, and the sum of the above components is 100%.

9. A method for preparing an intelligent anti-icing coating for a power transmission line according to any one of claims 1 or 8, characterized in that: The diameter of the graded heat storage and deicing filler is 100nm:1um, which is 5 to 1:

1. The silane coupling agent is any one of KH-570, KH-560, and KH-580. The solvent is any one of ethanol, DMF, and DMSO. The curing agent is any one of polyamide and tertiary amine. The defoaming agent is one of fatty alcohol ethoxysiloxane and polyether siloxane.

10. The method for preparing an intelligent anti-icing coating for a power transmission line according to claim 1, characterized in that: In step 4, the spraying speed is 10-30 m / min, the spraying distance is 20-50 mm, the curing time is 30-60 min, and the curing temperature is 50° C.-150° C.

Citation Information

Patent Citations

  • Anti-icing coating and anti-icing material, and preparation methods thereof

    CN110804395A

  • Phase-change micro-capsule with full-wave-band photo-thermal conversion function and preparation method thereof

    CN112251197A

  • Heat-conducting polymer composite material and preparation method thereof

    CN114427145A

  • Photo-thermal super-hydrophobic anti-icing and deicing coating and preparation method thereof

    CN116376414A

  • Preparation method of photo-thermal super-hydrophobic anti-icing and deicing composite coating

    CN117903665A

Cited By

  • Deicing material with low interface toughness coating coupled with mixed phase change material and preparation method of deicing material

    CN121652699A